Sistem Pendukung Keputusan Pemilihan Seorang Advokat Terbaik Menerapkan Metode MOORA - Martua Panggabean; Garuda Ginting (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The process of selecting a best advocate is not an easy thing, the problem with PERADI MEDAN in the process of selecting a best advocate is by appointing and selecting one of the advocates recommended by the leader of Dadi Peradi Medan based on criteria determined by Peradi, making it possible frequent errors and slow processing of prospective advocate data and the desired results have not been maximized because of inaccuracies in the selection process so that the results have an impact on the results of decisions given are not right. Based on the issue of the field cadre, researchers are interested in conducting research and determining the best advocate at Peradi Medan by using the Multiobjective Optimization On The Base Of Ratio Analysis (MOORA) method so as to be able to solve the problems faced by the cadre and clien in the selection of the best advocate . With the implementation of the MOORA method and the presence of a visual basic program can help and speed up the process of selecting the best advocate based on specified criteria, then what is chosen from the party for a best advocate is the highest value.